Functional Verification of Large-integers Circuits using a Cosimulation-based Approach - Nejmeddine Alimi; Younes Lahbib; Mohsen Machhout; Rached Tourki (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Cryptography and computational algebra designs are complex systems based on modular arithmetic and build on multi-level modules where bit-width is generally larger than 64-bit. Because of their particularity, such designs pose a real challenge for verification, in part because large-integer’s functions are not supported in actual hardware description languages (HDLs), therefore limiting the HDL testbench utility. In another hand, high-level verification approach proved its efficiency in the last decade over HDL testbench technique by raising the latter at a higher abstraction level. In this work, we propose a high-level platform to verify such designs, by leveraging the capabilities of a popular tool (Matlab/Simulink) to meet the requirements of a cycle accurate verification without bit-size restrictions and in multi-level inside the design architecture. The proposed high-level platform is augmented by an assertion-based verification to complete the verification coverage. The platform experimental results of the testcase provided good evidence of its performance and re-usability.